Association of antibodies to Plasmodium falciparum merozoite surface protein-4 with protection against clinical malaria. Issue 48 (4th December 2017) - Perraut, Ronald; Varela, Marie-Louise; Joos, Charlotte; Diouf, Babacar; Sokhna, Cheikh; Mbengue, Babacar; Tall, Adama; Loucoubar, Cheikh; Touré, Aissatou; Mercereau-Puijalon, Odile
Highlights: Facing drug resistance new effective malaria vaccines are required. Merozoite surface protein 4 is a major and essential component for parasite survival. MSP4 baculovirus-encoded protein showed high seroprevalence in endemic area. They were associated with clinical protection in active daily monitoring follow-up. Antibodies were associated with functional assay of merozoite phagocytosis by PNN. Abstract: Identification of parasite antigens targeted by immune effector mechanisms that confer protection against malaria is important for the design of a multi-component malaria vaccine. Here, the association of antibodies reacting with the Plasmodium falciparum merozoite surface protein-4 (MSP4) with protection against clinical malaria was investigated in a Senegalese community living in an area of moderate, seasonal malaria transmission. Blood samples were collected at the end of an 8-month long dry season without any recorded parasite transmission from 206 residents enrolled in a prospective follow-up study. Active daily clinical monitoring was implemented during the subsequent five months. Entomologic monitoring documented parasite transmission during the first three months of follow-up. Serum IgG levels were determined by ELISA against three MSP4 baculovirus-encoded recombinant protein constructs, namely the full-length MSP4p40, MSP4p30 devoid of a highly polymorphic sequence stretch and the conserved C-terminal EGF-containing MSP4p20, as well as against a merozoite crude extract. Community seroprevalence against all three constructs was quite high, the lowest being against MSP4p30. Seroprevalence and antibody levels against the three MSP4 constructs were age-dependent. IgG1 dominated the anti-MSP4p20 responses, while both IgG1 and IgG3 were observed against MSP4p40. Anti-MSP4 antibodies were associated with the antibody-dependent respiratory burst (ADRB) activity in a functional assay of merozoite phagocytosis by polymorphonuclear cells. Importantly, high antibody levels against each of the three MSP4 constructs at the end of the dry season were associated with reduced morbidity during the subsequent transmission season in an age-adjusted Poisson regression model (IRR = 0.65 [0.50–0.83], P < 0.001 for responses over the median values). These data are consistent with a protective role for the naturally acquired anti-MSP4 antibodies and support further development of MSP4 as a candidate component of malaria vaccine.